Advanced Monte Carlo simulations of emission tomography imaging systems with GATE. (14th May 2021) - Sarrut, David; Bała, Mateusz; Bardiès, Manuel; Bert, Julien; Chauvin, Maxime; Chatzipapas, Konstantinos; Dupont, Mathieu; Etxebeste, Ane; M Fanchon, Louise; Jan, Sébastien; Kayal, Gunjan; S Kirov, Assen; et al.
Abstract: Built on top of the Geant4 toolkit, GATE is collaboratively developed for more than 15 years to design Monte Carlo simulations of nuclear-based imaging systems. It is, in particular, used by researchers and industrials to design, optimize, understand and create innovative emission tomography systems. In this paper, we reviewed the recent developments that have been proposed to simulate modern detectors and provide a comprehensive report on imaging systems that have been simulated and evaluated in GATE. Additionally, some methodological developments that are not specific for imaging but that can improve detector modeling and provide computation time gains, such as Variance Reduction Techniques and Artificial Intelligence integration, are described and discussed.